Commercial Divers’ Subjective Evaluation of Saturation - Imbert, Jean Pierre; Balestra, Costantino; Kiboub, Fatima Zohra; Loennechen, Øyvind; Eftedal, Ingrid (Frontiers in Psychology, 2019)
Commercial saturation diving involves divers living and working in an enclosed atmosphere with elevated partial pressure of oxygen (ppO2) for weeks. The divers must acclimatize to these conditions during compression, and for up to 28 days until decompression is completed. During decompression, the ppO2 and ambient pressure are gradually decreased; then the divers must acclimatize again to breathing normal air in atmospheric pressure when they arrive at surface. We investigated 51 saturation divers’ subjective evaluation of the saturation and post decompression phase via questionnaires and individual interviews. The questions were about decompression headaches and fatigue; and time before recovering to a pre-saturation state. Twenty-two (44%) of the divers who responded declared having headaches; near surface (44%) or after surfacing (56%). 71% reported post-saturation fatigue after their last saturation, 82% of them described it as typical and systematic after each saturation. Recovery was reported to normally take from 1 to 10 days. The fatigue and headaches observed are compatible with divers’ acclimatization to the changes in ppO2 levels during saturation and decompression. They appear to be reversible post- decompression.